2018
DOI: 10.1111/ecc.12857
|View full text |Cite
|
Sign up to set email alerts
|

Do concordances of social support and relationship quality predict psychological distress and well-being of cancer patients and caregivers?

Abstract: This study examined concordances of cancer patients' received and caregivers' provided support and dyadic relationship quality, and their predictive utility in prospective psychological distress and well-being. A total of 83 Chinese cancer patient-caregiver dyads were recruited in two government-funded hospitals in Hong Kong. Participants reported received (patient)/provided (caregiver) emotional and instrumental support and dyadic relationship quality within 6 months after diagnosis (T1), and anxiety and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Future researchers should consider narrowing samples to specific cancer types. Cancers vary in their symptomology, prognoses, and treatment regimens, which may impact how patients and caregivers cope, thereby influencing their individual psychological health 4,11 . Studies' samples, methods, and analyses varied substantially, thus prohibiting a consensus on interdependence in dyads facing cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future researchers should consider narrowing samples to specific cancer types. Cancers vary in their symptomology, prognoses, and treatment regimens, which may impact how patients and caregivers cope, thereby influencing their individual psychological health 4,11 . Studies' samples, methods, and analyses varied substantially, thus prohibiting a consensus on interdependence in dyads facing cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer's impact on patients is multifaceted and has been well documented 1,2 . Caregivers (typically patients' friends or family 3 ) also experience deleterious effects from cancer, 2,4 and when caregivers' health is compromised, patients' health can be negatively impacted 5,6 . This premise is supported by an earlier systematic review by Meyler et al, 7 which found that dyad members' health tend to be interdependent .…”
Section: Introductionmentioning
confidence: 92%
“…A substantial body of evidence focused on the concordances between patient and caregiver/partner reports of the perceptions about symptom, cancer-related concerns and social support (Hou et al, 2018;Martinez et al, 2020;Silveira et al, 2010). A study showed that breast cancer patients' partners often tend to overestimate patients' self-reported levels of psychological distress (Carlson et al, 2001), indicating a lack of a shared understanding of patient distress.…”
Section: Introductionmentioning
confidence: 99%
“…The total score of SRQS of breast cancer survivors during chemotherapy is 54.49 (SD=5.84), which is consistent with the studies of Hou [9] in Hong Kong. Due to their unique cultural background, cancer patients in Asia normally pay more attention to support from family and friends and emphasize the importance of this support [31] than in European countries, which focus on maintaining the quality of couple relationships [32]. The reason may be that many breast cancer survivors are unable to accept the physical changes after mastectomy, lead to have a sense of inferiority.…”
Section: Discussionmentioning
confidence: 99%